Một số kết quả trên phụ thuộc mạnh - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
Strong dependencies have been introduced and axiomatized in [2,3,4]. In this paper, we give some results, that are related to strong dependencies. We give an algorithm for computing closures of one attribute in lineast arme O(p) where p is the length of S, and then we give a membership algorithm. We also give an algorithm for finding a minimal key and finding a set of all minimal keys of S.